Analisis Hadis-Hadis â€˜AshÃ¢bah dalam Konteks Kewarisan Islam (Studi Terhadap Pemaknaan dan Implementasi) - Darussamin, Zikri; Adynata, Adynata; Zailani, Zailani; Armansyah, Armansyah; Zikri, Ahmad (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Analysis of 'AshÃ¢bah Hadiths in the Context of Islamic Inheritance (A Study of Interpretation and ImplementationThe concept of 'asabah which is based on hadith â€œgive the inheritance to the rightful peopleâ€ (zÄwul furÏ‹d) and give the rest to the more primal of the male relativesâ€ is considered discriminatory by many parties as well as itâ€™s reducing the percentage of women's inheritance rights as heirs of dzawul furÃ»dh which have been determined in absolute terms (qaht'i). This paper aims to analyze the hadith about 'ashabah through the ma'anil hadith approach using the takhrÃ®j method as well as textual, contextual and intertextual interpretations. The results of the study concluded that the hadiths of 'ashabah are categorized as valid (sahih) hadiths and can be used as evidence (hujjah) regarding the legitimacy of the 'ashabah system in Islamic inheritance. The application of the â€˜asabah inheritance system does not have discriminatory implications. On the contrary, it actually contains the value of distributive justice, because justice in inheritance is not always measured by the similarity of designation between heirs, but is also determined by proportionality based on the size of the burden of responsibility assigned to each heir, the balance between rights and obligations and the balance between what is obtained with needs and uses. In order to measure the aspect of justice, the 'ashabah inheritance system must be understood integrally by placing the position of inheritance as a sub-system of the overall family law system within the Islamic legal system which is intact and comprehensive.